Simultaneous magnification of subtle motions and color variations in videos using Riesz pyramids - Fontanari, Thomas V.; Oliveira, Manuel M. (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2021)
Videos often contain subtle motions and color variations that cannot be easily observed. Examples include, for instance, head motion and changes in skin face color due to blood flow controlled by the heart pumping rhythm. A few techniques have been developed to magnify these subtle signals. However, previous techniques were targeted specifically towards magnification of either motion or color variations. Trying to magnify both aspects applying two of these techniques in sequence does not produce good results. We present a method for magnifying subtle motions and color variations in videos, which can be performed either separately or simultaneously. Our approach is based on the Riesz pyramid, which was previously used only for motion magnification. Besides modifying the local phases of the coefficients of this pyramid, we show how altering its local amplitudes and its residue can be used to magnify intensity/color variations. We demonstrate the effectiveness of our technique in multiple videos by magnifying both subtle motion and color variations simultaneously.